2022
DOI: 10.1039/d2ob01082h
|View full text |Cite
|
Sign up to set email alerts
|

Thioarylation of anilines using dual catalysis: two-step synthesis of phenothiazines

Abstract: A two-step synthesis of phenothiazines has been developed using a dual-catalytic ortho-thioarylation reaction of anilines as the key step. Activation of N-(2-bromophenylthio)succinimide was achieved using the super Lewis acid, iron(III)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…The development of this process was investigated using benzoyl-protected p -toluidine (Scheme 22 ). 48 Attempted thioarylation using iron(III) triflimide at 10 mol% loading and a 90 °C reaction temperature showed no reaction after 48 h. Based on our previous study, several Lewis bases were screened to promote and accelerate the transformation. Bis(4-methoxyphenyl)sulfane was again shown to be effective, generating the product in 88% yield.…”
Section: Synthesis Of Phenoxathiins and Phenothiazines Using Lewis Ac...mentioning
confidence: 99%
See 2 more Smart Citations
“…The development of this process was investigated using benzoyl-protected p -toluidine (Scheme 22 ). 48 Attempted thioarylation using iron(III) triflimide at 10 mol% loading and a 90 °C reaction temperature showed no reaction after 48 h. Based on our previous study, several Lewis bases were screened to promote and accelerate the transformation. Bis(4-methoxyphenyl)sulfane was again shown to be effective, generating the product in 88% yield.…”
Section: Synthesis Of Phenoxathiins and Phenothiazines Using Lewis Ac...mentioning
confidence: 99%
“…Using the diphenyl selenide accelerated thioarylation reaction, a two-pot process was developed for the synthesis of phenothiazines (Scheme 23 ). 48 For electron-rich anilines, N -protection was necessary to avoid competing N -thioarylation. Under the optimized conditions, clean and high-yielding thioarylation reactions were observed.…”
Section: Synthesis Of Phenoxathiins and Phenothiazines Using Lewis Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that iron(III) salts can act as Lewis acids for the activation of N -halosuccinimides and the subsequent regioselective halogenation of arenes . More recently, we have shown that iron(III) triflimide can activate N -thioaryl succinimides for the preparation of unsymmetrical biaryl sulfides . Based on this previous work, we proposed that an iron(III) salt may function as an activator of an N -thiocyanating reagent, allowing efficient thiocyanation of a wide range of arenes, without the requirement of acidic conditions or long reaction times.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, reported methods for the syntheses of [3,2- a ]­thiazoloindoles have typically involved the preparation of N- or C2-alkynyl-substituted indoles, followed by base-mediated cyclization . Instead, we proposed an alternative two-step approach, utilizing a regioselective C2-thioarylation of the tryptophan indole ring via iron­(III) and diphenyl selenide dual-catalyzed activation of N -thiosuccinimide 7 , followed by a copper-mediated N-arylation reaction between the ortho -bromide substituent and the adjacent indole amine (Scheme ). It was then proposed that the [3,2- a ]­thiazoloindole ring system could be extended, allowing substituent-based tuning of the photophysical properties, by regioselective bromination, followed by a Suzuki–Miyaura cross-coupling reaction.…”
mentioning
confidence: 99%